The emergence of novel infectious diseases and the public health impact of mass gathering events: risks and challenges (Nepal Journal of Epidemiology, 2022)
To date, there is the continuous emergence of novel infectious diseases endangering individuals' health and well-being worldwide. Over the past few decades, around forty contagious diseases, such as Severe Acute Respiratory Syndrome coronavirus-1 (SARS), Middle East Respiratory Syndrome coronavirus (MERS), Ebola, Zika, and newly, COVID-19 and Monkeypox outbreaks, have been reported globally. Zoonotic transmission is the major cause of these emerging infections in humans. These, whether caused by previously unknown pathogens or by those already well-known to science, heighten global concerns about the spread of communicable diseases and the resulting increase in death and disability.